Capturing alternate realities: visual metaphors and patient perspectives in graphic narratives on mental illness. Issue 5 (3rd September 2021) - Venkatesan, Sathyaraj; Saji, Sweetha
ABSTRACT: The diverse affordances of the medium of comics like spatio-temporality and visual rhetorical devices enable artists/patients who suffer from mental illnesses to approximate their experiential reality via graphic narratives. The graphic narratives analysed in this essay are reflections of the authors' experiences of dealing with friends and family members who suffer from mental conditions such as obsessive-compulsive disorder (OCD) and schizophrenia. Weaving together dreams, myths and reality, Nate Powell and Glyn Dillon create complex narratives that bring to life the patients' subjective worlds through the medium of comics. In so doing, these narratives vindicate the significance of graphic medicine in negotiating an alternate reality which is not captured in reductive biomedical and popular accounts of the illness conditions. Spatial and stylistic visual metaphors are used in these narratives to depict specific psychological experiences in viscerally engaging ways. Drawing theoretical insights from Elisabeth El Refaie, George Lakoff, and Mark Johnson, this essay explores the middle ground between triumphalist and fatalist narratives through grey metaphors that stylistically encapsulate the patient's lived experience. It also investigates how Powell's Swallow Me Whole and Dillon's The Nao of Brown use visual metaphors to intersperse multiple temporal and spatial dimensions that mimic patient's altered inner world.